Estimativa do risco de neoplasia maligna secundária em pacientes pediátricos tratados com radioterapia conformacional 3D - Melgarejo, Hidmer Laulate (2019)
The risk of secondary malignant neoplasms expressed as excess absoluter Risk (EAR) and excess relative risk (ERR) of lung and thyroid in pediatric patients treated with 3D conformational radiotherapy were estimated using models developed from a combination of epidemiological and radiobiological considerations and taking into account the non-homogeneous dose distribution. The dosimetric analysis shows the importance of treatment planning. Inadequate coverage and lack of conformity of the treatment target reflects high dose-volume parameters and ultimately the estimated risk. In the case of the EAR estimation of secondary malignant neoplasm of lung, the effect of the cellular repopulation process was not determinant, due to the form of doseresponse relationships and the dose used in pediatric patients. The ERR estimates for secondary malignant neoplasm of lung and thyroid show significant differences in relation to the age at exposure and attained age. The Monte Carlo simulation of treatment shows a non-significant difference relative to the risk of secondary malignant neoplasm of the lung and thyroid because the organs are in or near the treatment region.